2023
DOI: 10.1021/acs.jpcc.2c06545
|View full text |Cite
|
Sign up to set email alerts
|

Cation-Induced Disruption of the Local Structure of Water in Faujasite

Abstract: The changes in the structure of water confined in faujasite were resolved by a series of ab initio molecular dynamic simulations of explicit water molecules in faujasite with varying Si/Al ratio and counterions present. Radial distribution functions of water oxygen atom pairs, as well as counterions to Al pairs, were calculated to quantify the structure of water in faujasite and the distribution of counterions in the water-filled faujasite pores. Radial distribution functions reveal that confinement without co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 63 publications
0
3
0
Order By: Relevance
“…This peak at 2 Å suggests possible hydrogen bonding between neighboring water molecules (see Figure b). The RDFs (see Figure a and 1b) between O W and O W as well as O W and H W of confined water in FAU show a more intense peak compared to bulk water which is underpinned by the ab initio MD simulation study carried out by Shiery and Cantu . They have found that the confinement of water results in a more intense peak of O W –O W RDF (see Figure of Cantu’s study), which turns out to be more water–water hydrogen bonds in a confined system.…”
Section: Resultsmentioning
confidence: 84%
See 1 more Smart Citation
“…This peak at 2 Å suggests possible hydrogen bonding between neighboring water molecules (see Figure b). The RDFs (see Figure a and 1b) between O W and O W as well as O W and H W of confined water in FAU show a more intense peak compared to bulk water which is underpinned by the ab initio MD simulation study carried out by Shiery and Cantu . They have found that the confinement of water results in a more intense peak of O W –O W RDF (see Figure of Cantu’s study), which turns out to be more water–water hydrogen bonds in a confined system.…”
Section: Resultsmentioning
confidence: 84%
“…The RDFs (see Figure 1a and 1b) between O W and O W as well as O W and H W of confined water in FAU show a more intense peak compared to bulk water which is underpinned by the ab initio MD simulation study carried out by Shiery and Cantu. 42 They have found that the confinement of water results in a more intense peak of O W −O W RDF (see Figure 2 of Cantu's study 42 ), which turns out to be more water−water hydrogen bonds in a confined system. Laage and co-workers have found that water confined to the all-silica LTA zeolite shows a more intense peak of O W − O W RDF in comparison to bulk water and the intensity decreases with increasing density of confined water 38 (see Figure 2a,b of Laage's study 38 ).…”
Section: ■ Results and Discussionmentioning
confidence: 97%
“…93,94 These are increasingly computatioally difficult with increasing cation charges because more TI integration points would be needed to account for the rapid change in hydration structure as the local charge density increass; such calculations would constitute separate research projects and are not within the scope of this work. Calculating the absolute binding free energy of ions in nanoporous materials, like UiO-66 in our case, via AIMD potential-of-mean-force techniques, 75 is also problematic because AIMD simulation nanopore simulation cells seldom contain a bulk water reservoir region needed to yield the proper reference state for standard state binding free energies.…”
Section: Methodsmentioning
confidence: 99%
“…73,74 AIMD plus potential-of-mean-force (PMF) (including modern metadynamics variants) is a rigorous approach to calculate ion desorption free energies. [74][75][76][77][78][79] AIMD also permits the modeling of spontaneous proton transfer, including hydrolysis in the Ln 3+ first hydration shell that can accompany ion adsorption/ desorption.…”
Section: Introductionmentioning
confidence: 99%
“…84 In the work of Hack et al, 85 it was suggested that water trimer is the smallest cluster and a triply coordinated water molecule is the important structural motif to stabilize proton in zeolite pores. The acidic protons in water clusters usually have a high probability of moving away from the framework aluminum sites 75,82 or even entering into the water-filled pores 86 and the protonated water clusters can serve as the catalytically active species in different zeolites. 87 Similar to water dimer, the protonated water clusters comprising of high water loadings (e.g., 8 : 1 and 10 : 1 ratios of water to aluminum) are not stable and the acidic protons could move back to zeolite framework at elevated temperature.…”
Section: Brønsted Acidic Zeolitesmentioning
confidence: 99%